2023
DOI: 10.3390/ijms241411740
|View full text |Cite
|
Sign up to set email alerts
|

ARF3-Mediated Regulation of SPL in Early Anther Morphogenesis: Maintaining Precise Spatial Distribution and Expression Level

Abstract: Early anther morphogenesis is a crucial process for male fertility in plants, governed by the transcription factor SPL. While the involvement of AGAMOUS (AG) in SPL activation and microsporogenesis initiation is well established, our understanding of the mechanisms governing the spatial distribution and precise expression of SPL during anther cell fate determination remains limited. Here, we present novel findings on the abnormal phenotypes of two previously unreported SPL mutants, spl-4 and spl-5, during anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…For example, recent work by Zheng and colleagues demonstrated that auxin, a morphogen (Table 1) in plants, acts as a key factor in guiding male germ cell specification in Arabidopsis anthers [25]. This echoes the involvement of many factors that regulate organ polarity, which is also auxin-related, that also mediate germ cell formation by interacting with SPL/NZZ (e.g., YAABY, ETTIN) [102,103].…”
Section: Discussion and Perspectivesmentioning
confidence: 93%
“…For example, recent work by Zheng and colleagues demonstrated that auxin, a morphogen (Table 1) in plants, acts as a key factor in guiding male germ cell specification in Arabidopsis anthers [25]. This echoes the involvement of many factors that regulate organ polarity, which is also auxin-related, that also mediate germ cell formation by interacting with SPL/NZZ (e.g., YAABY, ETTIN) [102,103].…”
Section: Discussion and Perspectivesmentioning
confidence: 93%